2015
DOI: 10.5312/wjo.v6.i1.42
|View full text |Cite
|
Sign up to set email alerts
|

Current and future medical therapeutic strategies for the functional repair of spinal cord injury

Abstract: Spinal cord injury (SCI) leads to social and psychological problems in patients and requires costly treatment and care. In recent years, various pharmacological agents have been tested for acute SCI. Large scale, prospective, randomized, controlled clinical trials have failed to demonstrate marked neurological benefit in contrast to their success in the laboratory. Today, the most important problem is ineffectiveness of nonsurgical treatment choices in human SCI that showed neuroprotective effects in animal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 128 publications
0
43
0
8
Order By: Relevance
“…Numerous experimental studies have been reported with different success rates for SCI, however they have not been fully translated into the benefit of patients, both human and also companion animal (14,40). This can be related to many differences between models and clinical cases, including the ones encountered after naturally occurring spinal cord injury (14).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous experimental studies have been reported with different success rates for SCI, however they have not been fully translated into the benefit of patients, both human and also companion animal (14,40). This can be related to many differences between models and clinical cases, including the ones encountered after naturally occurring spinal cord injury (14).…”
Section: Introductionmentioning
confidence: 99%
“…An advantage is its ability to penetrate the blood-spinal cord barrier. We hypothesized that the acute treatment with CERE resulted in a) cell protection in the region of surgical spinal cord injury by the grafting procedure, b) neuroregeneration, and c) neuro-recovery within both the cord and graft, according to promising reports and evidence from brain and spinal cord lesions [18,19,22,23,28,31,[86][87][88][89][90][91][92][93][94].…”
Section: Discussionmentioning
confidence: 99%
“…Until now, traumatic paraplegia by severance of the spinal cord (SC) remains an irreversible condition. Basically, current clinical treatment strategies are targeted to promote axon regeneration and outgrowth beyond the scar formation following SC avulsion [1][2][3][4][5][8][9][10][11][12][13][14][15][16][17][18][20][21][24][25][26][27][28][29][30][31][72][73][74][75][76][77][78][79][80][81][82][83][84][85] Previous experimental and clinical studies together with GB have aroused some hope that paraplegic patients might achieve some selective voluntary muscle reinnervation after grafting the first motor neuron to skeletal hip muscles [10,11,25,72,73].…”
Section: Discussionmentioning
confidence: 99%
“…The principles of SCI treatments include early reduction and fixation, combined extramedullary and intramedullary decompression, cell transplantation, early rehabilitation treatment, and complication prevention. 3,8,9,12,13 Prehospital first aid About 25% of the neurological function impairment following spine injury is caused by improper handling; thus, first-aid management for SCI patients should be taken more seriously. The optimal way to handle an SCI patient is that three or more people from both sides or one side should lift the patient horizontally and place him/her on a flat board or a special stretcher, for transporting to specialized hospital by ambulance or helicopter.…”
Section: Treatmentsmentioning
confidence: 99%